2009
DOI: 10.1159/000251195
|View full text |Cite
|
Sign up to set email alerts
|

Acute-Onset Unilateral Psychogenic Hearing Loss in Adults: Report of Six Cases and Diagnostic Pitfalls

Abstract: We encountered 6 rare cases of acute-onset unilateral psychogenic hearing loss in adults. All were women in their 20s and 30s. Three cases had severe hearing impairment characterized by hearing loss at every frequency; 2 cases had profound hearing impairment, and 1 case had low-frequency hearing impairment. Of the 6 cases, 3 had a history of hearing loss, and 1 had a history of psychogenic visual disturbance. All 6 cases were initially diagnosed as having idiopathic sudden sensorineural hearing loss; all subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…In 2009, cases of sudden psychogenic deafness related to mental conditions were reported. 18 Contrera et al 19 found out that sudden deafness with moderate or severe conditions is related to the mood of elderly people and these patients also had different conditions of “Somatosensory impairment.” Long-term anxiety, depression and other mental issues may cause the autonomic nervous system to release more neurotransmitters such as norepinephrine and serotonin that lead to vasoconstriction, platelet activation, and blood viscosity increasing. These reactions will cause micro thrombosis and changes of physiological state, resulting in the inner ear microcirculation disorder, leading to sudden deafness by degeneration of the organ of Corti due to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, cases of sudden psychogenic deafness related to mental conditions were reported. 18 Contrera et al 19 found out that sudden deafness with moderate or severe conditions is related to the mood of elderly people and these patients also had different conditions of “Somatosensory impairment.” Long-term anxiety, depression and other mental issues may cause the autonomic nervous system to release more neurotransmitters such as norepinephrine and serotonin that lead to vasoconstriction, platelet activation, and blood viscosity increasing. These reactions will cause micro thrombosis and changes of physiological state, resulting in the inner ear microcirculation disorder, leading to sudden deafness by degeneration of the organ of Corti due to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…In psychogenic hearing loss, a discrepancy exists between the patient's subjective and objective audiological test results, such as a discrepancy between pure tone audiometry and auditory brainstem response. Although experienced clinicians may easily detect psychogenic hearing loss using conventional audiological procedures, more advanced audiological tests have been used to diagnose psychogenic hearing loss, including auditory brain responses and otoacoustic emissions 18 21 . In Taiwan, these subjective and objective audiological tests are widely available, enabling otolaryngologists to diagnose malingering, factitious disorder and psychogenic hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnoses of PHL, cochlear hearing loss, or retrocochlear hearing loss depended on the following tests: pure tone audiometry, otoacoustic emissions (OAEs), auditory brain response (ABR), and magnetic resonance imaging (MRI) [7]. Normal hearing level in pure tone audiometry was defined as <30 dBHL at all frequencies measured.…”
Section: Methodsmentioning
confidence: 99%